COVID-19 Pandemic: What can Nepal do to Curb the Potential Public Health Disaster? - Marahatta, Sujan Babu; Paudel, Shishir; Aryal, Neeta (Journal of Karnali Academy of Health Sciences, 2020)
COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the pandemic. Since its first report in late December from Wuhan, China, it has spread in 211 countries and has infected more than a million population claiming more than 81,000 lives until 7th April 2020. Although heterogeneous between countries, the recent trend shows that almost 10% of the infected persons are at the risk of death. The case-fatality has been reported to be at 2.3% in China, 7.2% in Italy, 1.73% in South Korea. One of the dreadful characteristics of the COVID-19 is that it is highly efficient at transmission from human to human. SARS-CoV-2 transmits from one human to another through respiratory droplets and close physical contact. Droplet transmission may also occur through fomites in the immediate environment around the infected person. Although there have been multiple studies and trials, no effective vaccines or anti-viral treatments have been effective to prevent or treat SARS-CoV-2 infection and can take another 12-18 months for the evidence to be generated. In this context, the only remained options would be to explore the epidemiological trend and learn from countries who have controlled the infection successfully. The early detection of cases and community containment have been some of the successful strategies. South Korea was able to lower the COVID-19 cases by an extensive and concerted community testing. The traditional strategies of isolation, quarantine, social distancing and community containment helped China to hold its level of infection after the second half of March 2020. With the increasing number of cases, Italy, the United State and the United Kingdom have increased their testing facilities. Germany, for instance, started mass testing and community surveillance quite early on (proactive community testing) reflected on its low fatality rate. In Nepal by 5 April 2020, only 1,521 tests have been performed only among the suspected cases (a reactive testing method) who attend the hospital and so far 9 has been confirmed cases. Though the case was identified in January, the country-wide lockdown came into effect only on 24 March 2020. Based on the report provided by the Ministry of Health and Population, Nepal is trying its best to increase the number of isolation and quarantine facilities along with the provision of essential PPE. Nepal is at stage II (evidence of local transmission as opposed to imported cases only) of a pandemic but it is difficult to say how the disease is circulating in our population due to poor testing coverage and no proactive community testing. Current public health measures that are cost-effective, although not ideal would be to stringently follow social distancing. Social distance alone would be futile unless, other measures are in place that includes proactive community testing, providing essential medical equipment such as personal protective equipment (PPE), isolation and quarantine spaces, medical logistics such as infection control gears, and ICU facilities with adequate ventilators. While social distancing is the best measure, for now, community outreach for proactive testing with mobilization of community health workers and the use of technologies to inform the preventive measures and to dispel the fears, and rumors can be promising. Including the general public, health workers and policymakers require a strong collaborative platform to work together to consolidate the measures ahead to prevent the COVID-19 disaster in Nepal.